Reconsidérer l’industrie « déjà là » : l’exemple des systèmes productifs territorialisés de la vallée du Gier - Clémentine Périnaud; Christelle Morel Journel (EchoGéo)
The Gier Valley, a highly industrialised territory located between Lyon and Saint-Étienne (France), is a complex geographical area made up of a string of small and middle-sized towns combining residential and industrial urban spaces. Here, the entrepreneurs’ strong local roots and the perpetuation of industrial production processes (especially in the metallurgy and mechanical sector) have ensured the relatively discreet continuation of dynamic productive systems based on small and medium-sized firms. The paper discusses the industrial sustainability of the Gier Valley, in relation to current and future urban renewal processes in a highly urbanised sector involved in a twofold metropolitan dynamic (Lyon and Saint-Étienne).